Turning south again : re-thinking modernism/re-reading Booker T. - Baker, Houston A., Jr., 1943- (e-Duke books scholarly collection., 2001)
Inaugurates a new southern studies with Black experience at the center, through a re-examination of the career of Booker T. Washington, showing incarceration to be the central characteristic of African-American life, even in the case of Tuskegee.